2017
DOI: 10.15237/gida.gd17050
|View full text |Cite
|
Sign up to set email alerts
|

Investigating the Physicochemical Properties and in Vitro Bioaccessibility of Phenolics and Antioxidant Capacity of Rooibos Herbal Tea Beverage

Abstract: In this research, production of novel beverages was planned and evaluation of physicochemical properties, total phenolics, antioxidant capacity, and bioaccessibility of products were aimed. Accordingly, 1% rooibos extract, citric and ascorbic acids, natural lemon flavor were added all types of beverages. Sucrose, agave, aspartame and acesulfame-K were respectively added to the beverages coded as RS, RA and RSW. Mixtures were plate filtered, filled into 200 mL glass bottles and pasteurized at 98 °C for 15 min. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 33 publications
1
6
0
1
Order By: Relevance
“…Besides, the FRAP assay had the highest (13.79%) bioaccesibility in comparison with DPPH (0.625%) and CUPRAC (0.095%). Suna [18] investigated the bioavailable phenolic and antioxidant capacity of rooibos tea. Differing from this study, the researchers identified higher bioaccesible antioxidant capacity in the CUPRAC assay.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Besides, the FRAP assay had the highest (13.79%) bioaccesibility in comparison with DPPH (0.625%) and CUPRAC (0.095%). Suna [18] investigated the bioavailable phenolic and antioxidant capacity of rooibos tea. Differing from this study, the researchers identified higher bioaccesible antioxidant capacity in the CUPRAC assay.…”
Section: Resultsmentioning
confidence: 99%
“…Samples taken from dried herbs were extracted (chemical extract) and beverage samples were obtained directly from the bottles. Phenolics and bioaccessible phenolics were examined as reported by Vitali et al [17], with slight adjustments made by Suna [18]. The simulation of gastrointestinal conditions using commercial digestive enzymes (pepsin and pancreatin) is commonly used to specify the potential availability of bioactives.…”
Section: Determination Of Phenolic Contents and Antioxidant Capacitymentioning
confidence: 99%
“…In beverages, not only the types of plant materials are important, but also the other ingredients used, such as sugar or its substitute. In the drink from Rooibos, drinks with sucrose were rated as the most favorite one in the sensory analysis, while the drink sweetened with agave was considered as most nutritious and beneficial (the greatest total antioxidant capacity) (Suna, 2017,). Some parameters, such as the antioxidant potential or pH, could also be influenced by other ingredients of the drink, such as citric acid (Sangmaet al, 2018,).…”
Section: Beverages Based On Tea or Herbsmentioning
confidence: 99%
“…Despite this, the latter drink was characterized by antioxidant activity at the level of 59.8 -73.71%. This activity depended on the proportion of the ingredients used (mint and chayote juice) (Sangma et al, 2018, Suna, 2017. Some plant materials fortified products in methylxanthines e.g.…”
Section: Beverages Based On Tea or Herbsmentioning
confidence: 99%
“…Örneklerin toplam asitlik değerleri, asetik asit cinsinden 1.21-1.35 g/100mL aralığında bulunmuştur (P <0.05). Benzer çalışmalardan elde edilen toplam asitlik değerleri sitrik asit cinsinden sırasıyla; 0.22 g/100mL (İncedayı, 2017), 0.17 g/100mL (Suna vd., 2018) ve 0.06 g/100mL (Suna, 2017) Baharat çaylarının en önemli özellikleri arasında antioksidan aktivite göstermeleri yer almaktadır (Almajano vd., 2008). Üretilen içeceklerin antioksidan kapasitesinin, eklenen elma sirkesi ile organik asitten kaynaklanabileceği düşünülmektedir.…”
Section: Sonuç Ve Tartişmaunclassified